Segmentation Based on Attitudes Toward Corporate Social Responsibility in Relation to Demographical Variables and Personal Values – Quantitative and Qualitative Study of Polish Consumers - Furman, Aleksandra; Maison, Dominika; Sekścińska, Katarzyna (Frontiers in Psychology, 2020)
The purpose of the present research was to create market segmentation of Polish consumers that would capture differences in reactions to Corporate Social Responsibility (CSR), taking into account sociodemographic data and consumers’ value structure. In order to better understand the extracted segments, a mixed method approach was adopted. The first quantitative study was conducted on a nationwide representative sample of Poles aged 18-55 years (N = 1055, CAWI survey). A subsequent qualitative stage covered 24 semi-structured in-depth individual interviews, with representatives of each segment identified in Study 1. Consequently, six segments of Poles were extracted and described, differing in knowledge, attitudes and beliefs about CSR: Sensible Optimists (15%), Sensitive Intellectuals (18%), Family Pragmatics (21%), Passive Poseurs (19%), Excluded & Frustrated (12%) and Corpo-Egoists (15%). The study showed both demographic and psychological differences in between segments. Segments with positive attitudes toward CSR are more female. Segment of least positive attitudes is manly and youngest one. However, results for age, education level and economic status are less conclusive. Personal values proved to be more useful in understanding different attitudes towards CSR than demography. Segments that are more open to CSR prize self-transcendence and maturity values, while less open segments are more oriented towards social status values.